BMI and Male Infertility: Impact on Sperm Parameters and Hormones: Hubungan antara Indeks Massa Tubuh dan Parameter Sperma, Hormon Reproduksi, dan Implikasinya terhadap Infertilitas Pria - Hussain Kh.Kadhem; Lamiaa Saoud Abbod Al-Anbagi; Mohammed Ali Hussein (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to assess the relationship between body mass index (BMI) and various indicators of men's reproductive health, specifically focusing on sperm parameters and levels of reproductive hormones, in individuals without recognized risk factors for infertility. The research employed a cross-sectional design, analyzing data from a sample of men. The results revealed a significant correlation between BMI and men's health indicators, demonstrating that BMI was associated with alterations in sperm parameters and reproductive hormone levels. Notably, BMI exhibited a negative connection with levels of both prolactin and testosterone. However, the findings emphasize the need for extensive, randomized, and prospective investigations to further elucidate the complex association between BMI and male infertility. These findings hold important implications for clinicians and researchers in the field, highlighting the importance of considering BMI as a potential risk factor for male infertility and advocating for additional research to inform diagnostic and therapeutic strategies targeting this population. Highlights: The study establishes a significant correlation between body mass index (BMI) and indicators of men's reproductive health, specifically sperm parameters and reproductive hormone levels. BMI demonstrates a negative association with prolactin and testosterone levels, highlighting the potential impact of BMI on male infertility. The findings underscore the importance of considering BMI as a potential risk factor for male infertility and emphasize the need for further research to inform diagnostic and therapeutic strategies Keywords : BMI, Male Infertility, Sperm Parameters, Reproductive Hormones, Risk Factors